Age estimation of adult human remains from hip bones using advanced methods - Kotěrová, Anežka; Navega, David; Štepanovský, Michal; Buk, Zdeněk; Brůžek, Jaroslav; Cunha, Eugénia (Forensic science international, 2018)
The assessment of age-at-death is an important and challenging part of investigations of human skeletal remains. The main objective of the present study was to apply different mathematical approaches in order to reach more accurate and reliable results in age estimation. A multi-ethnic dataset (n=941) of evaluated age-related changes on the pubic symphysis and the auricular surface of the hip bone was used. Two research groups examined nine different mathematical approaches. The best results were reached by Multi-linear regression, followed by the Collapsed regression model, with MAE values of 9.7 and 9.9 years, respectively, and with RMSE values of 12.1 and 12.2, respectively. The mean accuracy of decision tree models ranged between 30.7% and 72.3%, with the model using only the PUSx indicator performing the best. Moreover, our results indicate that the limiting factor of age estimation can be the visual evaluation of age-related changes. Further research is required to objectify the proposed methods for estimating age.
Keywords: Advanced mathematical methods; Humans; Pelvis; os ilium; lidé středního věku; neuronové sítě; Auricular surface; Age-at-death estimation; Female; Aged; mladý dospělý; dospělí; Visual assessment; Pubic symphysis; určení kostního věku; Neural Networks, Computer; senioři; lidé; Ilium; Models, Statistical; Adult; rozhodovací stromy; ženské pohlaví; Male; Decision Trees; Middle Aged; tělesné pozůstatky; Age Determination by Skeleton; Aged, 80 and over; statistické modely; Young Adult; senioři nad 80 let; Body Remains; mužské pohlaví; symphysis pubica; Pubic Symphysis